A piecewise regression approach for determining biologically relevant hydraulic thresholds for the protection of fishes at river infrastructure. Issue 5 (15th March 2016) - Boys, C. A.; Robinson, W.; Miller, B.; Pflugrath, B.; Baumgartner, L. J.; Navarro, A.; Brown, R.; Deng, Z.
Abstract : A piecewise regression approach was used to objectively quantify barotrauma injury thresholds in two physoclistous species, Murray cod Maccullochella peelii and silver perch Bidyanus bidyanus, following simulated infrastructure passage in a barometric chamber. The probability of injuries such as swimbladder rupture, exophthalmia and haemorrhage, and emphysema in various organs increased as the ratio between the lowest exposure pressure and the acclimation pressure (ratio of pressure change, R (NE:A) ) reduced. The relationship was typically non‐linear and piecewise regression was able to quantify thresholds in R (NE:A) that once exceeded resulted in a substantial increase in barotrauma injury. Thresholds differed among injury types and between species but by applying a multispecies precautionary principle, the maintenance of exposure pressures at river infrastructure above 70% of acclimation pressure ( R (NE:A) of 0·7) should protect downstream migrating juveniles of these two physoclistous species sufficiently. These findings have important implications for determining the risk posed by current infrastructures and informing the design and operation of new ones.